Altered SPECT 123I-iomazenil Binding in the Cingulate Cortex of Children with Anorexia Nervosa - Nagamitsu, Shinichiro; Sakurai, Rieko; Matsuoka, Michiko; Chiba, Hiromi; Ozono, Shuichi; Tanigawa, Hitoshi; Yamashita, Yushiro; Kaida, Hayato; Ishibashi, Masatoshi; Kakuma, Tatsuki; Croarkin, Paul E.; Matsuishi, Toyojiro (Frontiers in Psychiatry, 2016)
Several lines of evidence suggest that anxiety plays a key role in the development and maintenance of anorexia nervosa (AN) in children. The purpose of this study was to examine cortical GABA(A)-benzodiazepine receptor binding before and after treatment in children beginning intensive AN treatment. Brain single photon emission computed tomography (SPECT) measurements using 123I iomazenil, which binds to GABA(A)-benzodiazepine receptors, was performed in 26 participants with AN who were enrolled in a multimodal treatment program. Sixteen of the 26 participants underwent a repeat SPECT scan immediately before discharge at conclusion of the intensive treatment program. Eating behavior and mood disturbances were assessed using Eating Attitudes Test with 26 items (EAT-26) and the short form of the Profile of Mood States (POMS). Clinical outcome scores were evaluated after a 1-year period. We examined association between relative iomazenil binding activity in cortical regions of interest (ROIs) and psychometric profiles, and determined which psychometric profiles show interaction effects with brain regions. Further, we determined if binding activity could predict clinical outcome and treatment changes. Higher EAT-26 scores were significantly associated with lower iomazenil binding activity in the anterior posterior cingulate cortex (ACC). Higher POMS subscale scores were significantly associated with lower iomazenil binding activity in the left frontal, parietal cortex, and posterior cingulate cortex (PCC). “Depression-Dejection”, and “Confusion” POMS subscale scores, and total POMS score, showed interaction effects with brain regions in iomazenil binding activity. Decreased binding in the ACC and left parietal cortex was associated with poor clinical outcomes. Relative binding increases throughout the PCC and occipital gyrus were observed after weight gain in children with AN. These findings suggest that cortical GABAergic receptor binding is altered in children with AN. This may be a state-related change, which could be used to monitor and guide the treatment of eating disorders.